2014
DOI: 10.1016/j.jsat.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Legal factors associated with change in alcohol use and partner violence among offenders

Abstract: Intimate partner violence (IPV) is a pervasive social concern that may be exacerbated by high rates of alcohol dependence among perpetrators. Society has attempted to combat IPV through various legal interventions but the effects of specific legal factors on behavioral change and treatment compliance remain largely unexamined. The primary focus of the current study was to comprehensively evaluate the impact of various legal factors (i.e., judicial mandate, judicial monitoring, stage of change, and stake in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
2
8
0
3
Order By: Relevance
“…We found higher rates of NPV involvement than IPV involvement; this is consistent with other research that has examined both domains of violence in other SUD treatment settings (Chermack et al, 2009). The rates of both IPV and NPV in this sample were somewhat lower than those found in community or justicereferred samples Crane et al 2014), likely due to the higher mean age (48 years) and lower number of married couples in the present sample. The common presence of IPV and NPV highlights the importance of comprehensive screening for violence involvement in VA treatment clinics.…”
Section: Discussionsupporting
confidence: 89%
“…We found higher rates of NPV involvement than IPV involvement; this is consistent with other research that has examined both domains of violence in other SUD treatment settings (Chermack et al, 2009). The rates of both IPV and NPV in this sample were somewhat lower than those found in community or justicereferred samples Crane et al 2014), likely due to the higher mean age (48 years) and lower number of married couples in the present sample. The common presence of IPV and NPV highlights the importance of comprehensive screening for violence involvement in VA treatment clinics.…”
Section: Discussionsupporting
confidence: 89%
“…Volgens die ekologiese perspektief (Bronfenbrenner 1979;Pardeck 2015) is daar ʼn konstante wisselwerking tussen ʼn persoon en haar omgewing. As die omgewing nie ondersteunend is nie en vyandig is, veroorsaak dit stres soos die volgende narratiewe aandui: (2016) toon aan dat probleme in die omgewing soos ʼn gebrek aan hulpbronne kan lei tot alkohol-of dwelmmisbruik wat op die makrovlak kwesbare vroue negatief beïnvloed (Crane, Schlauch, Hawes, Mandel & Easton 2014;Pardeck 2015;Straussner & Isralowitz 2013).…”
Section: Tema 3: Uitdagings In Die Omgewingunclassified
“…It is worth noting that Fisher and Harrison (2013) describe this as co-dependent behaviour, where unhealthy patterns are developed in order to cover up for a father's alcohol misuse. The research (Crane, Schlauch, Hawes, Mandel & Easton, 2014;Klosterman & Chen, 2009) has also indicated that excessive drinking often leads to domestic violence. Although domestic violence can also occur when no drinking is involved, a large proportion of perpetrators are under the influence of alcohol at the time of the assault.…”
Section: "A Lot Of Domestic Violence Where There Was Domestic Violenmentioning
confidence: 99%